Identifying The Economic Potential And Improving The Competitiveness Of Lontong Artisans - Agung Bayu Murti; Erma Tri Wahyuningdyah (MediaTrend, 2023)
The general objective of this research is the existence of targeted strategies and policies related to efforts to increase competitiveness so that lontong craftsmen, especially Kampung Lontong MSEs in Kupang Krajan Surabaya, are able to compete and enter the Surabaya City culinary industry supply chain so as to increase economic growth in Surabaya City.In this study, the Asset-Process-Performance (APP) approach is used as the basis for developing a conceptual framework. The APP approach emerged as an idea that integrates various resources which then undergo a process and then produce performance as a unified measure of competitiveness (Momaya, 1998; Shee, 2002).The research method used is descriptive research using a survey. Descriptive research can be interpreted as a process of solving the problem being investigated by describing the state of the subjects and objects of research at the present time based on the facts that appear or how they are.The population in this study were all lontong craftsmen in Kampung Lontong RW 6 Kupang Krajan Village, namely 30 craftsmen and 17 people who were willing and able to be interviewed.The results showed that to increase competitiveness in terms of Assets is the need for training for entrepreneurs to increase their competence by mastering financial management and human resource management, while in terms of Process is to collaborate with academics in utilizing the results of research and development in orderly administration of human resources and organization even though the scale of business is still MSEs, include themselves and their employees when there is training and improve the ability to cooperate with lontong entrepreneurs in the fulfillment of material supply and marketing, finally in terms of Performance is the need for integration of the role of entrepreneurs, government and academics in research and development of technological innovation and new products.